2021
DOI: 10.1080/03323315.2021.1964564
|View full text |Cite
|
Sign up to set email alerts
|

Researching how student voice plays out in relation to classroom practice in Irish post-primary schools: a heuristic device

Abstract: This paper makes a novel and important contribution to scholarship by developing and presenting a set of concepts and questions for those researching student voice in Ireland to consider and explore in their studies, and specifically in relation to classroom practice at post-primary level. Here, a distinction is drawn between consultations that take place inside classrooms between students and teachers and consultations that take place between management and students and cognisance is paid to school patronage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…While student voice in Irish post-primary schools continues to focus on non-academic issues, as has recently been found elsewhere (see Brown et al 2020b), this research has shown that student voice is being used, to varying extents, in relation to classroom practice in Irish schools. The data presented here provide clear evidence that students in Irish post-primary schools are now being consulted on teaching and learning matters through what have been coined 'classroom-level consultations' and 'management-level consultations' (Skerritt, O'Hara, and Brown 2021). Classroom-level consultations involve teachers liaising with their students about classroom practice and the examples given during interviews include teachers seeking feedback on their teaching from students, students deciding on the classroom layout, and students choosing the texts to be studied.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…While student voice in Irish post-primary schools continues to focus on non-academic issues, as has recently been found elsewhere (see Brown et al 2020b), this research has shown that student voice is being used, to varying extents, in relation to classroom practice in Irish schools. The data presented here provide clear evidence that students in Irish post-primary schools are now being consulted on teaching and learning matters through what have been coined 'classroom-level consultations' and 'management-level consultations' (Skerritt, O'Hara, and Brown 2021). Classroom-level consultations involve teachers liaising with their students about classroom practice and the examples given during interviews include teachers seeking feedback on their teaching from students, students deciding on the classroom layout, and students choosing the texts to be studied.…”
Section: Discussionmentioning
confidence: 85%
“…It is important, however, that an extensive body of contextually sensitive knowledge be accumulated to enhance understandings of student voice in relation to classroom practice both in Ireland and beyond. Along with the data presented here, our heuristic device for researching student voice in relation to classroom practice (Skerritt, O'Hara, and Brown 2021) can be a suitable starting point for future work. Pearce and Wood (2019, 125) make the important point that 'student voice initiatives are necessarily grounded and sensitive to the local context'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participatory approaches employed in MYSTORY may offer a model for engaging young people to understand their unique perspectives on and experiences with school mental health and suicide prevention. Given the likelihood that student voice policies will considerably vary in both content and enactment across different types of schools ( Skerritt et al , 2021a ), we urge decision-makers to advocate for youth voice in school mental health policy in ways which recognizes schools’ needs.…”
Section: Discussionmentioning
confidence: 99%